Drug-induced hearing disorders: a disproportionality analysis of the FAERS database - Li, Baojian; Hu, Xiaoling; Yue, Zichen (Frontiers in Pharmacology, 2024)
Background To evaluate and identify reports of adverse events related to hearing impairment with drugs approved in the past 20 years, to identify new adverse reaction signals related to hearing impairment that have not yet been reported, and to improve the safety of drug treatments. Methods The adverse event report data from the FAERS database from the first quarter of 2004 to the fourth quarter of 2023 were retrieved. “Hearing disorders” was used as the keyword to screen for drugs related to the adverse event. After standardizing the drug name and the adverse drug event name, the adverse event reports with hearing disorders as the main suspect were collected, and the proportional imbalance algorithm was used to detect the potential adverse event signals to drug-related hearing impairment. Results The top five drugs with the highest number of reported adverse events to hearing impairment were sacubitril/valsartan (2,674), adalimumab (2,479), etanercept (1,834), tofacitinib (1,812), and apixaban (1,600). Except for adalimumab, the risk of hearing impairment is not mentioned in the instructions. The top five drugs for new signal strength are pancuronium (n = 13, ROR 67.57, PRR 53.61, IC5.74, EBGM 53.06), paromomycin (n = 6, ROR 46.3, PRR 39.33, IC5.30, EBGM 39.33), tafamidis (n = 300, ROR 14.90, PRR 14.13, IC3.82, EBGM 14.07), vildagliptin/metformin (n = 83, ROR 11.47, PRR 11.02, IC3.46, EBGM 11.01), and atorvastatin calcium/ezetimibe (n = 6, ROR 10.76, PRR 10.36, IC3.37, EBGM 10.36). Conclusion Our study covered 20 years of real-world data on reports of adverse events related to hearing impairment in the FAERS database, validating previous reports and studies, as well as identifying drugs that signal new adverse events of hearing impairment, especially some drugs commonly used for the treatment of chronic diseases (a combination of hypoglycemic drugs, antihypertensive drugs, and lipid modulators) and some new drugs in the 5-year post-market period.